Journey of Eye Banking in Nepal - Twyana, Shankha Narayan; Bajracharya, Leena; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2024)
Worldwide, over 10 million people are blind in one or both eyes from conditions affecting the cornea. Corneal transplantation surgery is the main treatment to restore vision in individuals with irreversible corneal blindness. However, in many countries, particularly in low- and middle-income countries (LMICs), the availability of cornea transplantation is low, due to limited supplies of corneal tissue. The global demand for tissue exceeds the supply, with only one cornea available for every 70 in need, and the short-fall even greater in LMICs.